An Alternative Synthesis Method for Di Calcium Phosphate (Monetite) Powders from Mediterranean Mussel (Mytilus galloprovincialis) Shells - (:unkn) unknown (SPRINGER, 2013)
Marine species, such as corals, sea shells and nacres, attract special interest in bioceramics field for bone graft, bone cements and drug delivery applications. Most of the marine structures are made up of pure calcium carbonate (calcite or aragonite) with a very small amount of an organic matrix. In the past the most common way to transform these structures to hydroxyapatite was hydrothermal transformation method. This current work introduces a new approach for producing fine powders of calcium phosphates from Mediterranean mussel (Mytilus galloprovincialis) shells. A comparative study was carried out to investigate the differences of these powders under only hot plate heating and hot plate heating together with ultrasonic agitation while H3PO4 was added. The temperature of the hotplate was kept constant at 80 degrees C and then, H3PO4 was added drop wise into the solution for 2 hrs. The mixture was then placed into an oven at 100 degrees C for 24 hrs. They were further calcined at 800 degrees C for 3 hrs. XRD, FTIR. and ICP-MS were used to identify the structure and composition. It was found that the final powders were predominantly monetite, with some tricalcium phosphate as a secondary phase. This relatively simple and efficient method can be easily applied to produce calcium phosphate precursor powders for a range of biomedical applications.
Keywords: Biomimetic; calcium phosphate powders; mechano-chemical; ultrasound; Mediterranean mussel Mytilus galloprovincialis; MECHANICAL-PROPERTIES; HYDROXYAPATITE; TEMPERATURE; SCAFFOLDS; APATITES